ON DYNAMICS INVERTED SPRING MASS SYSTEM - Khoerul Fata, Hafidh
The inverted spring mass system is constructed from a system consisting of a mass associated with three springs, each end of which is attached to a fixed position. The construction of this model produces a second order nonlinear differential equation. The character of the system without the intervention of external forces is conservative because it is a Hamiltonian system such that the orbits of the solutions are periodic. Then, with the addition of nonlinear external force intervention, the system solution leaves only one to two periodic solutions. However, whether using nonlinear external forces or not, the solution of the system is always bounded. The analysis results of perturbation method and numerical integration show that the amplitude of periodic solution and its number of periodic solutions that persist depends on the given . For the case of one persisting periodic solution, the amplitude of the periodic solution is linearly proportional to the given value of . Then, for the case of two persisting periodic solutions, the amplitude of the periodic solution will be inversely proportional to the given .